Kinerja Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Dalam Menanggulangi Rokok Ilegal Di Kota Makassar - Risnawati, Risnawati; Burhanuddin, Burhanuddin; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine the productivity, responsiveness adan responbility of the Office of Customs and Excise Supervision and Service in tackling illegal cigarets in Makassar City. This study used qualitative research. The number of informants were 5 people. Data collection techniques was data reduction, data presentasion and conclusion. The results of this study showed that performance of the customs and ExciseSupervision and Service Office was good. This could be seen in terms of productivity in terms of discipline and punishment was quite good in terms of employee attendance on time, and the imposition of penalties while in awarding was still lacking because there was no special award for employees. In terms of responsiveness in terms of debriefing, socialization and the program was quite good seen from the training, regular outreach and the existence of an illegal cigarette quake program. For the aspect of responsibility in terms of intelligence operations, market operatios as well as delegation of authority from the head of department to the head of office at the time of market operations.